Behavioral assessment of child-directed canine aggression. Issue 5 (4th October 2007) - Reisner, Ilana R; Shofer, Frances S; Nance, Michael L
Abstract : Objective: To characterize behavioral circumstances of bites to children by dogs presented to a veterinary behavior clinic. Methods: Retrospective case series examining medical records of dogs presenting by referral to a university veterinary hospital for aggression and which had bitten a child <18 years old. Behavioral data included age of victim, familiarity with dog, and circumstances of bites. Results: Records of bites to 111 children were examined. Children <6 years old were most commonly bitten in association with resource guarding (44%), whereas older children were most commonly bitten in association with territory guarding (23%). Similarly, food guarding was the most common circumstance for bites to familiar children (42%) and territory guarding for bites to unfamiliar children (53%). Behavioral screening of the 103 dogs examined revealed resource guarding (61%) and discipline measures (59%) as the most common stimuli for aggression. Anxiety screens revealed abnormalities in 77% of dogs. Potential contributory medical conditions were identified/suspected in 50% of dogs. When history before presentation was known, 66% of dogs had never previously bitten a child, and 19% had never bitten any human. Most dogs (93%) were neutered, and 66% of owners had taken their dogs to obedience training classes. Conclusions: Most children were bitten by dogs with no history of biting children. There is a high rate of behavioral abnormalities (aggression and anxiety) in this canine population. Common calming measures (neutering, training) were not routinely effective deterrents.